Typology and Effects of Co-opetition in Buyer–Supplier Relationships: Evidence from the Chinese Home Appliance Industry. (November 2014) - Liu, Yi; Luo, Yadong; Yang, Pianpian; Maksimov, Vladislav
Abstract: Building on the co-opetition perspective, this study takes a unified approach to examine relationship benefits and transaction costs in buyer–supplier relationships. We argue that buyer–supplier vertical dyads fall into one of four distinct co-opetition types based on their respective degrees of cooperation and competition. Each co-opetition situation then corresponds to unique levels of relationship benefits and transaction costs. A sample of 225 supplier–buyer dyads from the Chinese home appliance industry confirms that competition has a positive effect on transaction costs and a negative effect on relationship benefits, while cooperation stimulates greater relationship benefits but affects transaction costs mainly at low competition levels. The results advance prior research on buyer–supplier relationships and co-opetition and offer valuable avenues for future research.